Pendidikan Islam Abad ke-21: Antara Tantangan Global dan Penguatan Nilai Keislaman - Sukari, Sukari; Sayidah, Aminatus; Sriyanta, Sriyanta (TSAQOFAH, 2026)
Contemporary Islamic education faces complex challenges amid globalization, technological advancement, and socio-cultural change, which have generated a dichotomy between religious and general sciences, low educator quality, predominantly conventional teaching methods, and weak integration of Islamic values into students’ everyday lives. Unfiltered digital information flows also shape young people’s mindsets and behaviors, requiring Islamic education to function simultaneously as a moral safeguard and as a means of intellectual development that remains relevant to contemporary demands. At the institutional and policy levels, these challenges are further reflected in limited facilities and infrastructure, suboptimal educational management, and insufficient curricular innovation that is adaptive to the needs of modern society. This article argues that renewal and strengthening of the Islamic education system should be pursued through improving educator quality, developing an integrative curriculum that bridges religious and general sciences, and using technology judiciously to support learning processes. Accordingly, Islamic education is expected to cultivate a generation with noble character, broad knowledge, and the capacity to respond proactively to contemporary challenges without losing its Islamic identity.